Recuerdos de Filipinas: las islas vistas por el periodista y escritor español Francisco Cañamaque (1851—1891) - Valera Villalba, Lorena (Romanica Silesiana)
Spanish journalist, politician and writer, Francisco Cañamaque, worked for nine months in 1873 in the Spanish Philippines as a member of the Spanish government. During this period, he wrote down his impressions about the islands and their society, and then published Recuerdos de Filipinas (1877). His book is divided into two different parts: in the first one, he describes satirically the society of the islands, and in the second one, he proposes some reforms to improve the social situation in the colony and to make the metropolis obtain more benefit from it. Although some writers heavily criticized the satire, the cruel, exaggerated, description of the islands might be an important part of the strategy used by Cañamaque to make the government take a more active role in the administration of the islands. Key words: Spanish Philippines, Francisco Cañamaque, Francisco Entrala, Patricio de la Escosura, Spanish colonies, Recuerdos de Filipinas.